DEVELOPMENT OF MULTIMEDIA ANIMATION BASED ON AUTODESK INVENTOR TO IMPROVE GENERIC SKILLS OF SCIENCE IN KINEMATIC ACCELERATION COURSE - Pratama, Deden Ramdani; Ariyano, Ariyano; Komaro, Mumu (Journal of Mechanical Engineering Education, 2020)
Student learning outcomes over the past four years show that more than half the number of students get a fairly low value. This condition occurs due to many factors, one of which is the learning process that still uses the lecture method and the use of simple learning media. This study aims to produce the development of Autodesk Inventor based multimedia animation on kinematics acceleration material, as well as to find out the increase in students' generic science skills on kinematics acceleration material.This research uses the ADDIE development method, and uses the Pre Experimental Design research design with the type of One Group Pretest-Posttest Design. This study was conducted on 25 samples of Mechanical Engineering Education students in 2015. The application of generic science syntax in this study consisted of modeling, symbolic language, causal law, logical consistency, observation, and awareness of scale. The results obtained showed that there was an increase in the generic science skills of studentsafter the implementation of Autodesk Inventor-based multimedia animation on kinematics acceleration material. This is evidenced by the average N-gain value of students of 0.63 in the medium category. The highest increase in generic science skills occurredin the observation aspect with an N-gain value of 0.65, and the lowest increase occurred in the aspect of symbolic language with an N-gain value of 0.52 which was included in the medium category.